Strengthening Religious Moderation through Islamic Spirituality at State Senior High School 1 Binjai - Aulia, Mizar; Syarif, Fauzi Ahmad; Rodhiyah, Siti; Albina, Meyniar (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Strengthening religious moderation It is important to instill religious moderation in the younger generation such as school students. Because in fact, there are many cases where students have a radical understanding of religion. in religion, this happens due to the indoctrination of radical ideas to students through da'wah institutions at school. Therefore, researchers formulated this research with the title "Strengthening Religious Moderation through Islamic Spirituality at SMA Negeri 1 Binjang Through Islamic Spirituality at SMA Negeri 1 Binjai". The purpose of the research is to outline the function of Islamic Spirituality in strengthening religious moderation, know the form of implementation of strengthening religious moderation through Islamic Spirituality and describe the implications of strengthening religious moderation through the Islamic Spirituality at SMA Negeri 1 Binjai. The method used in the research is descriptive qualitative research is a method used to research the conditions of objects that occur naturally and at the same time the researcher becomes the key instrument. becomes the key instrument. Data collection techniques are done through observation, interviews and documentation studies. Data analysis is done with interactive analysis techniques. interactive analysis techniques. The results showed that Islamic Spirituality functions strategically in strengthening religious moderation at SMA Negeri 1 Binjai, the implementation of strengthening religious moderation is carried out with the activities of Romansa Greeting and proselytizing campaigns via YouTube and social media, the implications can be seen by the increase in students' religious moderation in the environment. can be seen by the increase in students' religious moderation attitudes in the school environment.